THE PRACTICE OF FUTSAL AS A TOOL FOR TEACHING AND LEARNING MATHEMATICS CONTENT (Fiep Bulletin - online, 2015)
This research aims to seek an improvement in the quality of teaching and learning of Mathematics content. The present study related the Pythagorean Theorem and the sport practice of the futsal to demonstrate its effectiveness on student's development. This research has a qualitative approach that characterized itself descriptively.  At that, it was conducted with a sample with 38 students of two classes of 9th grade at a school in Mossoró city. We collected the data through intensive direct observation procedure, and we used a questionnaire and diagnostic activities. After collecting the data we can observe how important is the interaction of the courses for teaching and learning process, once that students had a greater interest in the classroom.
Keywords: Pythagorean Theorem; futsal and teaching-learning process.